Research hotspots and trend analysis of abdominal pain in inflammatory bowel disease: a bibliometric and visualized analysis - Peng, Shuai; Xia, Yuan; Wang, Ying; Yu, Xiaoyun; Wu, Zunan; Zhang, Li; Xu, Ke; Shen, Lei; Luo, Hesheng (Frontiers in Pharmacology, 2023)
The study aimed to provide a bibliometric and visual analysis of research on abdominal pain in inflammatory bowel disease and discuss the current status, research hotspots, and future developments.We used the Web of Science Core Collection to comprehensively search the literature on abdominal pain-related research in IBD published between 2003 and 2022.The bibliometric and visual analysis was performed through CiteSpace, VOSviewer software, R language, and the bibliometric online analysis platform, including authors, institutions, countries, journals, references, and keywords in the literature.A total of 3503 relevant articles are included, indicating that the number of articles in this field has increased in recent years. The USA leads the way with a dominant position in terms of article output, followed by China and JAPAN. USA (967 articles), University of Calgary (98 articles), and World Journal of Gastroenterology (127 articles) are the top publishing countries, institutions, and journals, respectively; keyword analysis shows that gut microbiota, depression, stress, visceral hypersensitivity, and multidisciplinary approach are the hot spots and trends in this research area.Abdominal pain-related studies in IBD have received increasing attention in the past two decades. This study provides the first bibliometric analysis of papers in this research area using visualization software and data information mining. It provides insights into this field's current status, hot spots, and trends. However, many outstanding issues in this research area still need further exploration to provide a theoretical basis for its clinical application.